(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
There are various methods through which educational institutions can help foster and develop general skills in students. General skills refer to transferable abilities that are not specific to a single subject area but are applicable across multiple disciplines and useful for students’ future careers and lives. Some of the key methods that schools and teachers can employ to effectively form general skills in their students are discussed below.